Validation Procedures for the Determination of the Indicator «Bacterial Endotoxins» - O. V. Shapovalova; P. V. Shadrin; N. P. Neugodova; O. V. Gunar; G. V. Dolgova (Антибиотики и Химиотерапия)
The use of the LAL test as a method for determining bacterial endotoxins (BE) allows us to normalize the content of impurities causing a pyrogenic reaction in patients. Increasing the reliability and reproducibility of this method is promoted by validation procedures, which are an integral part of the methods for determining BE and are based on the construction of a «model experiment» where the test and control samples are compared. Depending on the test procedure (gel-clot or photometric tests) for determining the presence of BE, appropriate validation procedures are used to assess the necessary parameters. The purpose of the study: to prove the possibility of interchangeability of the methods for determining BE with the help of validation procedures on the example of the drug «Ceftriaxone powder for intramuscular injection 500 mg». Research techniques: Gel-clot and Kinetic Chromogenic tests. The results of the conducted tests confirm the reproducibility and specificity of the LAL test methods. The sensitivity of the LAL reagent used is confirmed. In the experiments of the gel-clot test for Ceftriaxone, a dilution of 1:160 of the base solution in the concentration of 100 mg/ml was validated. The parameters of the calibration curve in the Kinetic Chromogenic test corresponded to the validation requirements (CV0.98). Determination of the bacterial endotoxin content in Ceftriaxone by the photometric method is possible at the same 1:160 dilution, where the accuracy of determination of the BE in the test sample is